Analogi Hukum Harta Bersama Perkawinan Islam Dengan Konsep Ekonomi Islam (Syirkah) - Mumaddun Khaerudin Salami; Meriza Elpha Darnia; Tike Murti Sari Dewi (Riau Law Journal, 2025)
Marriage is one of the rights of every person; the right to marry is protected by the 1945 Constitution of the Republic of Indonesia, article 28B paragraph 1. Meanwhile, marriage according to Islamic law is a commandment of Allah and the sunnah of the Prophet Muhammad. The marriage contract in marriage aims to unite two people in a sacred bond that has the value of worship. However, even though it is bound by the marriage contract, it does not immediately unite the assets of both parties, assets obtained before marriages remain the personal property of each party. Meanwhile, regarding assets obtained during marriage or joint assets as explained in Law Number 1 of 1974 concerning marriage. Islam does not recognize the concept of joint assets, and then the concept of joint assets was formulated by the government and scholars in Indonesia as written in the Compilation of Islamic Law (KHI) allowing the implementation of joint assets by equating the legal issues with the concept of "syirkah" which was previously only known in Islamic economics. The purpose of this writing is to understand and analyze how the concept of "syirkah" can be used in cases of joint assets in Islamic marriages. The method used in this study is a descriptive normative method. The normative approach is legal research that uses secondary data sources, while the descriptive approach is a research method that attempts to describe and interpret conditions according to what they are.